Dhu they or don't they? A study of sound production by three fish species of commercial and recreational importance in Western Australia - Parsons, Miles; Lewis, P.; Longbottom, Simon; McCauley, Robert; Fairclough, D. (Acoustical Society of Australia, 2012)
Over 800 species of fish produce sound, for a variety of reasons including distress, spawning and agonistic behaviour. An increasing number of sparids have been shown to be soniferous, but while studies of glaucosomatids (pearl perches) have shown the presence of likely 'sonic' muscles confirmed reports of sound production in the wild has been elusive. In Western Australia, a project examined whether West Australian dhufish (Glaucosoma hebraicum), snapper (Pagrus auratus) and black bream (Acanthopagrus butcheri) produce sound. Recordings of dhufish, an iconic fish in Western Australia, have provided proof of sound production and some acoustic characteristics of dhufish sounds are presented. For black bream, while sounds were recorded at a known spawning location at a time of spawning, black bream could not be confirmed as the source. No confirmed evidence of sound production was found for snapper, either during spawning or upon capture. It is possible that in data-limited situations for fisheries, monitoring of sound-producing fishes using passive acoustic techniques could elucidate additional information about ecology, reproductive behaviour and relative abundance.